Record-Breaking Rain Event Altered Estuarine Viral Assemblages - Alaina C. Woods (Microorganisms, 2022)
Viruses are the dominant biological entity in the ocean, play a vital role in biogeochemical cycles, and provide their hosts with novel metabolic capabilities through auxiliary metabolic genes (AMGs). Hurricane Harvey was a category 4 hurricane that made landfall on the Texas coast in 2017 and lashed the Houston area with 1.4–1.7 × 1010 m3 of rainfall. In this paper, we aim to characterize how the changes in abiotic conditions brought by Hurricane Harvey altered the viral assemblages of Galveston Bay at the taxonomic level and determine how viral ecosystem functions were altered. Metagenomes of the viruses and their hosts were sequenced from a transect in Galveston Bay over the five weeks following the storm. Our results show that the viral assemblages of Galveston Bay dramatically changed following Hurricane Harvey’s landfall. Of the abiotic parameters measured, salinity had the strongest effect on shaping the viral assemblages. In the five weeks following Hurricane Harvey, there was a steady increase of metabolic genes and putative viral infections. Our study provides the first in-depth look at how marine viral assemblages respond and recover from extreme rainfall events, which models predict will become more frequent and intense with climate change.